A sales tax is better at promoting healthy diets than the fat tax and the thin subsidy - Zarko Kalamov (Health Economics, 2020)
We analyze how a sales tax levied on all food products impacts the consumption of healthy food, unhealthy food, and obesity. The sales tax can stimulate the consumption of healthy meals by lowering the time costs of food preparation. Moreover, the sales tax lowers obesity under more general conditions than a tax on unhealthy food (fat tax) and a subsidy on healthy food (thin subsidy). We calibrate the model using recent consumption and time use data from the US. The thin subsidy is counterproductive and increases weight. While both the sales tax and the fat tax mitigate obesity, the former imposes a lower excess burden on consumers.
Keywords: 330; fat tax; obesity; sales tax; thin subsidy